2021
DOI: 10.1038/s41398-020-01165-x
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a clinical service to prevent psychosis: What, how and when? Systematic review

Abstract: The first rate-limiting step to successfully translate prevention of psychosis in to clinical practice is to establish specialised Clinical High Risk for Psychosis (CHR-P) services. This study systematises the knowledge regarding CHR-P services and provides guidelines for translational implementation. We conducted a PRISMA/MOOSE-compliant (PROSPERO-CRD42020163640) systematic review of Web of Science to identify studies until 4/05/2020 reporting on CHR-P service configuration, outreach strategy and referrals, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 126 publications
4
76
2
1
Order By: Relevance
“…This meta-analysis is based on a large dataset encompassing 75 studies and 5,288 CHR-P individuals. The mean age of 20 years and minimally higher frequency of males (55.5%) in the CHR-P individuals of the meta-analysed cohorts is consistent with the typical sociodemographic profile of this group [11] . The large number of studies identified indicates that, as well as transition to psychosis, other outcomes are increasingly being evaluated in prospective studies of CHR-P subjects.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This meta-analysis is based on a large dataset encompassing 75 studies and 5,288 CHR-P individuals. The mean age of 20 years and minimally higher frequency of males (55.5%) in the CHR-P individuals of the meta-analysed cohorts is consistent with the typical sociodemographic profile of this group [11] . The large number of studies identified indicates that, as well as transition to psychosis, other outcomes are increasingly being evaluated in prospective studies of CHR-P subjects.…”
Section: Discussionsupporting
confidence: 83%
“…However, two recent meta-analyses of randomised controlled trials conducted in CHR-P individuals found that antipsychotics were not superior to other interventions for improving APS [ 24 , 60 ]. It is also likely that antipsychotics are initially prescribed to those CHR-P individuals who have higher levels of APS [ 11 , 61 ] and are perceived as being at higher risk of developing psychosis, and therefore have more chances to display relative improvements over follow-up time. Although in the past antipsychotics have been compared to placebo in CHR-P individuals [47] , they are currently not recommended by clinical guidelines for CHR-P individuals due to the lack of preventive evidence and low benefit to risk ratio [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many mental health services have tried to address this discontinuity of care [63,64], significant gaps remain. Future mental health reforms could leverage and refine clinical high-risk services for young people at risk of psychosis, which typically accepts referrals aged 14-35 years and therefore provide essential transitional care to this vulnerable young population [15,17,58].…”
Section: Discussionmentioning
confidence: 99%
“…For example, young people with attenuated symptoms for psychosis [10][11][12][13] and functional impairments accumulate several risk factors and have a 25% probability of developing the disorder over 3 years [14]. Clinical care for these individuals is typically implemented in specialised clinical services [15][16][17][18] and has the potential to delay or impede the transition to psychosis, although the efficacy of preventive interventions awaits more robust evidence [19][20][21]. Targeted preventive approaches involve screening programmes in asymptomatic individuals who have significant risk factors for certain psychiatric disorders [7,22,23] (primary selective prevention [7,8]) or public health campaigns in the general population (primary universal prevention) [7,8,24].…”
Section: Introductionmentioning
confidence: 99%